DROSERA SPECIES OF UKRAINIAN FLORA - Rak Олександр; Buzunko Петро; Solokha Іванна (Biota. Human. Technology, 2022)
Article’s purpose. Investigation of geographical distribution, ecological and coenotic features of habitats and protection of Drosera species. Methodology. Field studies were conducted in 2014-2015 by using the route recognition method. Mapping schemes for distribution of Drosera species in the territory of Ukraine were made on the basis of literature analysis, on the results of herbarium data processing of M. M. Grishko National Botanical Garden of NAS of Ukraine (KWHA), M. G. Kholodnyi Institute of Botany (KW), Rivne Regional Museum of Local Lore (ROKM) and data from the Global Biodiversity Information Fund (GBIF). Scientific novelty. Expeditions revealed atypical locations of D. rotundifolia and D. intermedia. In the hydrological nature reserve of the national importance «Ozero Sviate» (Chernihiv region, Kozelets district) D. intermedia grows together with Nymphaea candida. This is explained by the further overgrowth of the lake and its transformation into a meso-oligotrophic swamp. In the Rivne Nature Reserve, D. rotundifolia was found at the forest road passing through a swampy pine forest. D. rotundifolia grows at the road epiphytically, on old logs of pine, which covered the forest path. Unusual ecological-cenotic conditions of species growth can be explained by the fact that there is no competition for food and light with representatives of the Ericales order on the road, and wood is a good conductor of rain moisture. Conclusions. It was found that there are 39 known species locations for Drosera rotundifolia, 40 – for D. intermedia, 26 – for D. anglica, and 3 species locations for D. obovata in the terrytory of Ukraine. In regard that all species of Drosera genus are endangered stenotopic species of sphagnum swamps or of other rare biotopes and all species of the genus except Drosera rotundifolia are listed in the Red Book of Ukraine, we propose to include Drosera rotundifolia to the new edition of the Red Book of Ukraine in the category «vulnerable».